2005
DOI: 10.1161/01.str.0000158923.19956.73
|View full text |Cite
|
Sign up to set email alerts
|

Functional Recovery in Aged and Young Rats After Embolic Stroke

Abstract: Background and Purpose-Advanced age is associated with a decrease in brain plasticity compared with the young adult.Sildenafil, a phosphodiesterase type 5 (PDE5) inhibitor promotes brain plasticity and improves functional outcome after stroke in the young animal. Here, we test the hypothesis that sildenafil provides restorative therapeutic benefit to the aged animal. Methods-Male Wistar rats (aged, 18-month old; young, 3-month old) were subjected to embolic stroke. Saline or sildenafil was administered daily a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
164
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(173 citation statements)
references
References 27 publications
6
164
2
1
Order By: Relevance
“…30,45,62,68,83 Lastly, when cerebral blood flow to an area decreases to ischemic levels, sildenafil has demonstrated the ability to decrease the size of the infarct and improve outcomes by promoting angiogenesis in hypoxic areas. 14,66,[87][88][89] Each of these pathways represents future areas of study in determining sildenafil's role in treating DCI.…”
Section: Sildenafil As Treatment For DCImentioning
confidence: 99%
See 1 more Smart Citation
“…30,45,62,68,83 Lastly, when cerebral blood flow to an area decreases to ischemic levels, sildenafil has demonstrated the ability to decrease the size of the infarct and improve outcomes by promoting angiogenesis in hypoxic areas. 14,66,[87][88][89] Each of these pathways represents future areas of study in determining sildenafil's role in treating DCI.…”
Section: Sildenafil As Treatment For DCImentioning
confidence: 99%
“…In studies of SAH in animals, sildenafil has shown to reduce plasma levels of endothelin-1, 9,25,26,44,47,55,60,64,65 limit platelet induced microthrombosis, 30,45,62,68,83 and promote cerebral angiogenesis in hypoxic areas. 14,66,[87][88][89] Sildenafil has been extensively studied and proven safe in both healthy and cardiovascularly ill patients. 1,5,18,24,35,41,67,80,81,90,91 However, to date there have been no studies in humans providing rigorous data on the safety of sildenafil in the setting of SAH.…”
mentioning
confidence: 99%
“…88 Treatment of stroke with sildenafil starting at 24 hours after stroke significantly increased brain levels of cGMP, evoked neurogenesis, and reduced neurological deficits after stroke in both young adult and aged rats. 86,89 Increasing age decreases the number of new neurons in the dentate gyrus and the SVZ. 90 Sildenafil not only enhances angiogenesis and neurogenesis in young adults, but also augments angiogenesis and neurogenesis in aged ischemic rats.…”
Section: Pde-5 Inhibitors Cgmp and No Donorsmentioning
confidence: 99%
“…9 -10 Administration of sildenafil, therefore, by inhibiting cGMP breakdown, causes intracellular accumulation and increased brain levels of cGMP. [11][12][13] Previous studies showed that treatment of rats with sildenafil significantly increased the cortical levels of cGMP in both hemispheres for nonischemic rats, 12 and in the ipsilateral hemisphere at 7 days after stroke compared with levels in control animals. 13 Elevated cGMP levels in cerebral tissues may be involved in promoting angiogenesis during recovery up to 4 weeks after embolic stroke in rats.…”
mentioning
confidence: 97%